DEVELOPMENT AND VALIDITY OF ROLE-PLAYING-BASED STUDENT WORKSHEETS ON ADDICTIVE SUBSTANCES - Syaifuddin, Ahmad; Kuswanti, Nur (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2026)
This research is motivated by the science learning process that still uses conventional methods. Another problem found is the lack of application of learning methods that involve students and the perceived difficulty of addictive substance material by students. One solution to this problem is to use the role playing method. This study aims to develop role playing-based worksheet on addictive substance material based on validity. The study uses the ADDIE development model which consists of the stages of analysis, design, development, and evaluation. The instrument used in this study is a validation sheet. The subjects of this study were teachers, material and media experts and lecturers. The data collection technique used was a validity test from several validators. The validation results based on the assessment of three validators of the product that had been developed were included in the very valid category with an average score of 3.76 in the didactic aspect. The construction requirements in terms of identity obtained an average of 4.00, language obtained an average of 3.88, and content obtained an average of 3.97 categorized as very valid with a score still above 3.25. Based on the technical requirements that include the appearance of the cover and images have an average score of 3.95 categorized as very valid because it is above 3.25. While in terms of worksheet characteristics it is categorized as very valid with a score of 4.00.